Identification, characterization, and determinants of dietary patterns of low-income urban adults in Vietnam and Nigeria - Pastori, Giulia; Maasen, Kim; Talsma, Elise F.; Verhoef, Hans; Samuel, Folake O.; Shittu, Oluyemisi F.; Huong, Le Thi; Hernandez, Ricardo; Wertheim-Heck, Sigrid; Le, Xuan Thi Thanh; Mai, Truong Tuyet; Lundy, Mark; et al. (Elsevier, 2025)
Understanding dietary patterns and their determinants can steer efforts to food systems transformations required to provide sustainable healthy diets. Based on 24-h recall data and using latent class analysis, we characterized dietary patterns of adults from low-income neighborhoods in Hanoi, Vietnam and Ibadan, Nigeria (n = 385 and 344, age 18–49 years). We examined sociodemographic determinants and diet quality (diversity, non-communicable disease risk, and micronutrient adequacy) of these patterns. Three dietary patterns were identified in each country. Vietnamese patterns differed in sociodemographic characteristics and diet quality. Nigerian patterns differed in diet quality but not in sociodemographics. Understanding different consumer groups and the drivers of consumption helps to identify tailored interventions to diversify diets and improve diet quality.